Violation of principles and defendant’ guarantees in the Units against Flagrante Delicto - Agip Vásquez, José Leonides (2022)
The purpose of this article is to describe the reality on the application of immediate proceedings and the possible violation of principles and defendant’s guarantees in the cases resolved in the Units against Flagrante Delicto. Accordingly, an analysis of the existing regulations and the casuistic on immediate proceedings in flagrante delicto will be carried out, which will evidence the violation of the defendant’s rights, and will conclude on the need to reform the procedural rule establishing the procedures for the Units against Flagrante Delicto to follow.